CONTROL OF RIGIDITY OF AN ELASTIC ELEMENT ACTIVE VIBROSUPPORT - Kulyk, Mykola; Kvasnikov, Volodymyr (Proceedings of National Aviation University (archive), 2013)
The device and control system for reduction of influencing of vibration from the power-plant with bearing spirally on the fuselage of helicopter are offered. It is shown, that the management by inflexibility of resilient element provides possibility of more flexible and effective construction of algorithm of management by the system of active vibroprotection.